Neuroendocrine Tumour of the Breast in a Young Lady: A Case Report - Abidin, Zainal Adwin Zainal; Hayati, Firdaus; Azizan, Nornazirah; Saladina, Jasmin Jaszle (Bangladesh Journal of Medical Science, 2019)
Primary neuroendocrine tumours of the breast are rare. The WHO has classified them according to the tissue grading. The clinical presentation is similar to the usual infiltrating ductal carcinomas, however the histopathological assessment requires special staining to confirm the diagnosis of neuroendocrine tumour. We report a case of a primary neuroendocrine tumour of the breast in a 33-year-old lady who presented with a locally advanced breast tumour with multicentric disease. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.419-422